Computing All Elliptic Curves Over an Arbitrary Number Field with Prescribed Primes of Bad Reduction. Issue 1 (2nd January 2019) - Koutsianas, Angelos
ABSTRACT: In this article, we study the problem of how to determine all elliptic curves defined over an arbitrary number field K with good reduction outside a given finite set of primes S of K by solving S -unit equations. We give examples of elliptic curves overQ and quadratic fields.